Case Report: A Unique Case of Pediatric Central Nervous System Embryonal Tumor Harboring the CIC–LEUTX Fusion, Germline NBN Variant and Somatic TSC2 Mutation: Expanding the Spectrum of CIC-Rearranged Neoplasia - Hu, Wanming; Wang, Juan; Yuan, Li; Zhang, Xing; Ji, Yuhang; Song, Chao; Zeng, Jing; Sun, Xiaofei (Frontiers in Oncology, 2020)
Central nervous system (CNS) embryonal tumors (WHO grade IV) are a heterogeneous group of rare, poorly differentiated neuroepithelial malignant neoplasms that commonly occur in children, and they have a poor prognosis. The 2016 WHO (World Health Organization) classification of CNS tumors created a major shift in paradigm of the classification of embryonal tumors. However, some cases were still difficult to classify. Further integrative genomic analysis is needed to improve the precise classification, diagnosis and treatment of CNS embryonal tumors. Herein, we firstly report a case of CNS embryonal tumor harboring the pathogenic CIC–LEUTX gene fusion. A 2-year-old male infant presented with a solid cystic mass in the left temporal lobe-basal ganglia and left parietal lobe (maximum diameter, 75mm) and underwent gross tumor resection. The tumor was classified as a poorly differentiated embryonal neoplasm of neuroectodermal origin that lacked specific features and rosettes. By immunohistochemistry, the tumor cells were strongly positive for synaptophysin, and the Ki67 proliferation index was high (>50%). FISH (Fluorescence in situ hybridization) results indicated no change in the copy number at the 19q13.42 C19MC locus. Next generation sequencing showed a CIC–LEUTX gene fusion, a somatic TSC2 c.G2714A mutation, and a heterozygous germline NBN c.C127T mutation. One month after surgery, there was recurrence of the intracranial tumor (maximum diameter, 55 mm) as well as spinal cord implantation metastasis. The patient received chemotherapy (CTX+CBP+VCR/DDP+VP-16), radiotherapy, and a drug targeting the TSC2 gene (everolimus). At the time of this writing, the patient is alive without evidence of disease for 11 months. This is the first report of the CIC–LEUTX gene fusion in a case of CNS embryonal tumor.